A Guide to the project management body of knowledge Project Management institute - USA Project Management institute (usa PMI Book Service Center, 2008)
Standard language has been incorporated throughout the document to aid reader understanding, New data flow diagrams clarify inputs and outputs for each process,Greater attention has been placed on how Knowledge Areas integrate in the context of Initiating,Planning, Executing, Monitoring & Controlling, and Closing process groups,wo new processes are featured: Identify Stakeholders and Collect Requirements
The fourth edition has been updated to incorporate the most current knowledge and practices the project management. It focuse on improved consistency, clarity, and readability to facilitate understanding and implemention.Data flow diagrams for each process have been refined and reconfigured. the new edition also includes an appendix that addresses key interpersonal skills that a project manager utilizes when managing a project
An American National Standrad
Includes indexes
Keywords: Corporate culture; Management; Organizational behavior; Strategic planning